Diplomado de Recipientes a Presión: Módulo VI (Inspección y Pruebas de Recipientes a Presión Conforme a la Sección VIII, Div.1 del Código ASME) - Rivera Mendoza, Orlando R. (My University, 2007)
The objectives of The National Board are to promote: -Uniform administration and enforcement of boiler and pressure vessel laws. -Standardize construction. -Standardize operation. -Standardize inspector qualification. -Safety valve testing for valves built to the A.S.M.E -
Keywords: Recipientes a presión; Certificate, inspection, inspector, tests, mechanical tests, SA-20, marking requirements, SA-178/SA-209, SA-450, UG-94, SA-370, welding electrodes, welding materials, UG-84(j) rejection, repairs of materials, UG-93, UG-77, compliance, welds, radiography, welded joints, ultrasonics, liquid penetrant, pressure testing, hydrostatic, pneumatic